Inventory credit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Inventory credit: an approach to developing agricultural markets by J Coulter and A Shepherd 1995 107pp ISBN 92 5 103703 5